A DFT study of structures and stabilities of isomeric furo-, thieno-, and selenophenopyridines. (3rd April 2017) - Aliveisi, Rahman; Taherpour, Avat (Arman); Yavari, Issa
GRAPHICAL ABSTRACT: ABSTRACT: The structures, electronic properties, and chemical reactivities of isomeric furo-, thieno- and selenophenopyridines have been studied by B3LYP/6-31G( d ) method. The optimized geometries of these isomers show planar configurations. The structural properties such as bond lengths, bond angles, and dipole moments of these isomers were calculated. The energies of frontier molecular orbitals (HOMO and LUMO) are used to determine several chemical reactivity parameters as a measure of their relative stabilities. These include total energy ( E ), ionization potential ( I ), electron affinity ( A ), chemical hardness (η), chemical softness ( S ), electronic chemical potentials (μ), and electrophilicity (ω). Selepheno[3, 4- c ]pyridine possesses the highest electrophilicity and minimum chemical hardness among the calculated isomeric structures. The largest calculated dipole moment belongs to furo[2, 3- c ]pyridine, while thieno[3, 2- b ]pyridine has the lowest.